A gold-catalyzed acid-assisted regioselective cyclization for the synthesis of polysubstituted oxazoles - Wang, Qian; Hoffmann, Stephanie; Schießl, Jasmin; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (European journal of organic chemistry, 2020)
Polysubstituted oxazole derivatives are obtained through a regioselective gold-catalyzed reaction of α-alkynylamides and alkynoates in the presence of nitriles. The intermediary obtained gold carbenes are generated by alkyne oxidation with a pyridine N-oxide. Acidic conditions ensure that only one of the two carbonyl oxygen atoms in these intermediates selectively cyclizes to the products in excellent yields.
Gesehen am 18.05.2020